Non-traumatic neurological emergencies: imaging of cerebral ischemia. - Grunwald, I; Reith, W (2002)
Cardiovascular disease is the leading cause of death worldwide with almost one-third of all cardiovascular deaths ascribed to stroke. Imaging modalities, such as CT, MRI, positron emission tomography (PET), and single photon emission CT (SPECT) provide tremendous insight into the pathophysiology of acute stroke. Computed tomography is considered the most important initial diagnostic study in patients with acute stroke, because underlying structural lesions, such as tumor, vascular malformation, or subdural hematoma, can mimic stroke clinically. Diffusion-weighted imaging (DWI) has the ability to visualize changes in diffusion within minutes after the onset of ischemia and has become a powerful tool in the evaluation of patients with stroke syndrome. Territories with diffusion and perfusion mismatch may define tissues at risk, but with potential recovery. An alternative strategy with CT technology uses rapid CT for dynamic perfusion imaging, with similar goals in mind. Angiography can be performed in the hyperacute stage if thrombolytic therapy is being considered. Indications for diagnostic angiography include transient ischemic attacks in a carotid distribution, amaurosis fugax, prior stroke in a carotid distribution, a high-grade stenotic lesion in a carotid artery, acquiring an angiographic correlation of magnetic resonance angiography (MRA) or computed tomographic angiography (CTA) concerning stenotic findings. In 50% of all angiograms performed in the hyperacute stage, occlusion of a vessel is observed; however, the need for angiography has been made less necessary due to the improvements of MRA, duplex ultrasound, and CTA. Numerous etiologies can lead to infarction. In children, pediatric stroke is very uncommon. The most common cause is an embolus from congenital heart disease with right-to-left shunts. Also a dissection of large extracranial vessels may result in cerebral infarction, and although the brain is equipped with numerous venous drainage routes, the occlusion of a large sinus or a widespread vein obstruction will eventually lead to venous infarction. Thus, optimal stroke care requires not only early and exact identification of ischemia, but also a close collaboration between the clinician and radiologist.